PERANCANGAN SISTEM INFORMASI INVENTORY BERBASIS WEB PADA GUDANG DI PT. SPIN WARRIORS - Renaldy Gosal; Anton Rustam (Aisyah Journal Of Informatics and Electrical Engineering (A.J.I.E.E), 2022)
Inventory system is a system that is used to insert inventory data into the database so that there are no errors in input, output, and report generation data based on the desired data as needed, and stored according to certain rules in a ready-to-use state and stored in the database. Inventory System is done by Waterfall method which is a systematic system information development model. Data mining methods used were observation and literature study. The programming used is programming website using MySQL and PHP. The inventory system is thought to be able to help the warehouse staff of PT. Spin Warriors in monitoring stock, searching for data, and making reports. With the implementation of this system, it is expected to reduce errors that may occur in the warehouse of PT. Spin Warriors.